AB0758 Change in Weight from Baseline during the Palace Clinical Trial Program with Apremilast, an Oral Phosphodiesterase 4 Inhibitor: Pooled Results from 3 Phase 3, Randomized, Controlled Trials. (10th June 2014) - Mease, P.; Gladman, D.; Kavanaugh, A.; Adebajo, A.; Gomez-Reino, J.; Wollenhaupt, J.; Schett, G.; Shah, K.; Hu, C.; Stevens, R.; Edwards, C.; Birbara, C.
Abstract : Background: PALACE 1, 2, and 3 assessed the efficacy/safety of apremilast (APR) in pts with active PsA despite prior DMARDs and/or biologics. Objectives: Assess weight change from BL in PALACE 1, 2, and 3. Methods: Pts were randomized 1:1:1 to PBO, APR 20 mg BID (APR20), or APR 30 mg BID (APR30) stratified by baseline DMARD use (yes/no). Pts with <20% reduction from BL in SJC or TJC at Wk 16 were required to be re-randomized to APR20 or APR30 if initially randomized to PBO, or continued on their initial APR dose. At Wk 24, all remaining PBO pts were re-randomized to APR20 or APR30. The pooled analysis comprises data for the PBO-controlled period (Wks 0 to 24) and the APR-exposure period (Wks 0 to ≥52) up to cutoff date, 3/1/2013. Results: During the PBO-controlled period, 495 pts received PBO, 501 received APR20, and 497 received APR30. At cutoff, 720 pts had received APR20 and 721 had received APR30. At BL, mean/median weight was 86.4/84.0 (PBO), 86.1/84.0 (APR20), and 84.5/83.0 (APR30) kg. Weight decrease was reported as an AE in a small proportion of pts during the PBO-controlled (PBO: 0.4%; APR20: 1.0%; APR30: 1.4%) and APR-exposure (APR20: 1.4%; APR30: 1.8%) periods. No pts in the PBO-controlled period and 2/1441 pt (APR20, 1; APR30, 1) in the APR-exposure period discontinued due to weight decrease. Weight loss has been reported with other PDE4 inhibitors. An additional analysis using observed weight measurements collected at selected visits assessed any changes from BL weight. In the PBO-controlled period, most pts remained within 5% of their BL weight (PBO: 92.1%; APR20: 83.5%; APR30: 86.4%). A larger proportion of APR-treated pts experienced weight loss (APR20: 57.9%; APR30: 56.8%) vs PBO (40.1%). Weight loss >5% was experienced by 3.9% (PBO), 12.7% (APR20), and 11.0% (APR30) (Table). At the end of the PBO-controlled period, mean/median weight change from BL was 0.09/0.0 (PBO), -1.16/-0.60 (APR20), and -0.96/-0.60 (APR30) kg. In the APR-exposure period (Wks 0 to ≥52), most pts remained within 5% of BL weight (APR20: 77.0%; APR30: 75.8%); 57.3% (APR20) and 57.1% (APR30) experienced weight loss. Weight loss did not lead to any overt medical sequelae or manifestations through the APR-exposure period. In an analysis to determine the relationship between weight loss and gastrointestinal (GI) AEs, weight loss was not associated with diarrhea or nausea/vomiting. Conclusions: APR was associated with a low rate of weight decrease reported as an AE. The incidence of observed weight loss was higher with APR vs PBO, although most pts remained within 5% of their BL weight. Observed weight loss did not appear to be dose-dependent and did not lead to overt clinical sequelae. No association between weight loss and incidence of other AEs, including GI AEs, was apparent. Disclosure of Interest: P. Mease Grant/research support: for Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, and UCB, Consultant for: Celgene Corporation, Novartis, and Roche, D. Gladman Grant/research support: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer Inc, Novartis, and UCB, A. Kavanaugh Grant/research support: Abbott, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor-Janssen, Pfizer Inc, Roche, and UCB, A. Adebajo: None declared, J. Gomez-Reino Grant/research support: Roche and Schering-Plough, Consultant for: Bristol-Myers Squibb, Roche, Schering-Plough, and Wyeth, Speakers bureau: Bristol-Myers Squibb, Pfizer Inc, Roche, Schering-Plough, and UCB SA, J. Wollenhaupt: None declared, G. Schett Grant/research support: Abbott, Celgene Corporation, Roche, K. Shah Employee of: Celgene Corporation, C. Hu Employee of: Celgene Corporation, R. Stevens Employee of: Celgene Corporation, C. Edwards Grant/research support: Celgene Corporation, Pfizer Inc, Roche, and Samsung, Speakers bureau: Abbott, Glaxo-SmithKline, Pfizer Inc, and Roche, C. Birbara Grant/research support: Amgen, Bristol-Myers Squibb, Incyte, Eli Lilly, Merck, and DOI: 10.1136/annrheumdis-2014-eular.2391